Assessment of economic feasibility and risk of a small scale bean production unit in the Municipality of Campo Mourão - Silveira, Glauber Flaviano (2014)
Due to the importance of family farming especially in bean cultivation in the state of Paraná, Brazil, current assay evaluates the economic viability and risk of bean production on a family farm in Campo Mourão (northwestern region). Economic viability indicators have been assessed, such as net present rate value (NPR), internal rate of return (IRR) and payback period (PP). Further, sensitivity analysis and risk analysis were carried out with Monte Carlo simulation method. Results indicated the project´s economic viability. Moreover, their viability was more sensitive to revenue components than that of costs. These factors did not warrant significant risk to the project´s success.